Prevalence of violence against women in the Northeast: a public health issue - Martins, Renata Torres; Silva, Macerlane de Lira; Quental, Ocilma Barros de; Gabriel, Igor de Sousa (Brazilian Journal of Production Engineering, 2020)
Introduction: Violence against women is a global phenomenon that does not respect race, religion or social class. It is characterized by the use of words or actions that hurt as people and can result in injury, suffering and even death. It is a major social problem that knows no geographical barriers and is spreading throughout the world. Objective: Analyze the prevalence of violence against women in the Northeast and its impacts on public health. Methodology: an integrative literature review, in which the LILACS and SCIELO databases were used for research through Health Sciences Descriptors. As inclusion criteria, they were selected as publications in Portuguese and English, available in full and included in the time frame of the last 7 years. Conclusion: the results showed that violence against women is a serious social problem, but that every day it also becomes a serious public health problem. The services offered by Primary Health Care are essential for the identification of occurrences of violence against women. For the identification process to be successful, it is necessary that the health professionals responsible for care are trained. Many doctors, nurses and responsible health workers are not familiar with the topic. There are also professionals who readily identify the situation of violence, but feel powerless. Very often, the victim does not consider that a problem of domestic violence should be analyzed and recognized as a problem related to the health system.
Keywords: Violence; Woman; Public health.